Correlation between flexibility of chain-like polyelectrolyte and thermodynamic properties of its solution - Sajevic, T.; Reščič, J.; Vlachy, V. (Condensed Matter Physics, 2011)
Structural and thermodynamic properties of the model solution containing charged oligomers and the equivalent number of counterions were studied by means of the canonical Monte Carlo simulation technique. The oligomers are represented as (flexible) freely jointed chains or as a linear (rigid) array of charged hard spheres. In accordance with the primitive model of electrolyte solutions, the counterions are modeled as charged hard spheres and the solvent as dielectric continuum. Significant differences in the pair distribution functions, obtained for the rigid (rod-like) and flexible model are found but the differences in thermodynamic properties, such as, enthalpy of dilution and excess chemical potential, are less significant. The results are discussed in light of the experimental data an aqueous polyelectrolyte solutions. The simulations suggest that deviations from the fully extended (rod-like) conformation yield slightly stronger binding of counterions. On the other hand, the flexibility of polyions, even when coupled with the ion-size effects, cannot be blamed for qualitative differences between the theoretical results and experimental data for enthalpy of dilution. Структурнi та термодинамiчнi властивостi модельного розчину, що мiстить зарядженi олiгомери i еквiвалентну кiлькiсть протиiонiв, вивчалися за допомогою канонiчного моделювання Монте-Карло.
Олiгомери представленi у виглядi (гнучких) вiльноз’єднаних ланцюжкiв або як лiнiйний (жорсткий) ланцюг заряджених твердих сфер. Вiдповiдно до примiтивної моделi розчину електролiту, протиiони моделюються як зарядженi твердi сфери, а розчинник враховується через дiелектричнi властивостi середовища. Виявлено значнi вiдмiнностi у парних функцiях розподiлу, отриманих для жорсткої та гнучкої моделей, але вiдмiнностi в термодинамiчних властивостях, таких як, ентальпiя розведення i надлишковий хiмiчний потенцiал, є менш значними. Отриманi результати обговорюються з точки зору експериментальних даних для водних розчинiв полiелектролiтiв. Результати моделювання по-казують, що вiдхилення вiд повнiстю витягнутої (стрижневої) конформацiї веде до сильнiшого зв’я-зування протиiонiв. З iншого боку, гнучкiсть полiiонiв, навiть у поєднаннi з впливом розмiрiв iонiв, не може бути причиною якiсних вiдмiнностей мiж теоретичними i експериментальними результатами для ентальпiї розведення.